The relationship between the parents' parenting activities and the habit of watching educational programs with the moral values - Ika Noviana (Jurnal Prima Edukasia, 2018)
This study aims to examine: (1) the relationship between parenting style with moral values, (2) the relationship between habits of watching educational television with moral values, and (3) the relationship between parenting style and habits of watching educational television with moral values among the fifth grade elementary school group of Puren Condongcatur Depok Sleman. This research is a nonexperimental quantitative. The research sample is 149 students of the fifth grade elementary school group of Puren Condongcatur Depok Sleman. The results showed: (1) There is a positive and significant relationship between parenting style with moral values indicated by r 0.812 rtable 0.159 and p 0.05. (2) There is a positive and significant relationship between habits of watching educational television with moral values indicated by r 0.731 rtable 0.159 and p 0.05. (3) There is a positive and significant relationship between parenting style and habits of watching educational television with moral values indicated by r 0.841 rtable 0.159 and F 176.828 Ftable 3.06.